Barriers to Asset Recovery : An Analysis of the Key Barriers and Recommendations for Action - Stephenson, Kevin M.; Gray, Larissa; Power, Ric; Brun, Jean-Pierre; Dunker, Gabriele; Panjer, Melissa (World Bank, 2012)
Theft of public assets from developing countries is an immense problem with a staggering development impact. These thefts diverts valuable public resources from addressing the abject poverty and fragile infrastructure often present in such countries. Although the exact magnitude of the proceeds of corruption circulating in the global economy is impossible to ascertain, estimates demonstrate the severity and scale of the problem at $20 to $40 billion lost to developing countries each year. What this estimate does not capture are the societal costs of corruption and the devastating impact of such crimes on victim countries. Theft of assets by corrupt officials, often at the highest levels of government, weakens confidence in public institutions, damages the private investment climate, and divests needed funding available for core investment in such poverty alleviation measures as public health, education, and infrastructure. This study's key objective is to mobilize policy makers on the existing difficulties in stolen asset recovery actions and convince them to take action on the featured recommendations. Such action will enhance the capacity of practitioners to successfully recover stolen assets.